Use of a PHBQ Test for Evaluation of Psychosomatic Disorders in 3—7-year-old Children in the Perioperative Period - V. V. Milenin; K. R. Tolasov (Общая реаниматология, 2013)
This paper validates the PHBQ test that has been thrice translated from English into Russian; then its three variants translated into English again. The variant whose meaning was the most significant was taken for further patient testing and researches. To confirm that the translated variant was a systemic tool for work with patients, it was compared with modified PHBQ and CBCL tests for 3—7-year-old children. The latter has been translated into Russian and is commercial. The statistical significance of each of these tests was estimated using different statistical data processing methods, such as a factor analysis, a reliability analysis (Cronbach’s alpha), a correlation and regression statistical analysis that is used to test the validity of different mathematical models. The findings may suggest that the Russian language-adapted test may be employed as a reliable tool for patient testing in detecting post-hospitalization disorders; the correlation observed in the comparison of the three tests being rather high. Key words: post-hospitalization syndrome, surgical interventions, fear, distress, PHBQ test.